Factors determining the outcome of children hospitalized with severe pneumonia - Broor Shobha; Pandey Ravindra M; Lodha Rakesh; Tiewsoh Karalanglin; Kalaivani M; Kabra Sushil K (BMC, 2009)
Abstract Background Pneumonia is one of the leading causes of morbidity and mortality in under fives. We carried out a comprehensive study to identify factors influencing both mortality and morbidity for children less than 5 years of age hospitalized with severe pneumonia. Methods 200 hospitalized children aged 2-60 months with World Health Organization (WHO) defined severe pneumonia were enrolled in the study. The children were managed using a standard protocol. They were closely followed up for need for change in antibiotics, prolonged hospital stay, need for mechanical ventilation and mortality. Data on the factors influencing the outcome were collected. Results Of 200 children enrolled in the study, 113 (56.5%) needed a change in antibiotics, 102 (51%) stayed for more than 5 days in the hospital, 41 (20.5%) needed mechanical ventilation and 21 (10.5%) died. On multivariate analysis, lack of exclusive breastfeeding [RR (95%CI) 2.63 (2.16-2.86)], overcrowding [RR (95%CI) 1.94 (1.35-2.38)] and an abnormal chest x-ray [RR (95%CI) 2.29 (1.22-3.44)] were associated with the need for change of antibiotics. Lack of exclusive breastfeeding [RR (95%CI) 2.56 (2.0-2.93)], overcrowding [RR (95%CI) 2.59 (1.78-3.23)] and an abnormal chest x-ray [RR (95%CI) 2.99 (1.65-4.38)] were identified as determinants for prolonged hospital stay. Head nodding [RR (95%CI) 8.34 (2.71-12.77)], altered sensorium [RR (95%CI) 5.44 (1.34-17.56)], abnormal leukocyte counts [RR (95%CI) 5.85(1.36-17.14)] and pallor [RR (95%C) 10.88 (2.95-20.40)] were associated with mortality. Head nodding (RR (95% CI) 4.73 (1.50-6.36)] and cyanosis (RR (95%CI) 5.06 (1.80-11.34)] were the determining factors for mechanical ventilation. In radiographically confirmed pneumonia, the determining factors for change of antibiotics were: lack of exclusive breast feeding [RR (95% CI) 2.05 (1.69-2.2)] and low birth weight [RR (95% CI) 1.59 (1.1-1.89)]. For prolonged hospital stay, the factors identified were mothers' education less than graduation [RR (95% CI) 1.5 (1.19-1.7)], lack of exclusive breast feeding [RR (95% CI) 1.77 (1.19-2.09)] and oxygen saturation of < 90% at time of presentation [RR (95% CI) 2.06 (1.42-2.42)]. Determinants for mechanical ventilation were mothers' education less than graduation [RR (95% CI) 3.6 (1.15-6.3)] and cyanosis at presentation [RR (95% CI) 10.9 (1.56-18.9)]. For mortality, the only determinant was pallor [RR (95% CI) 10.54 (1.8-21.79)]. Conclusion Children hospitalized with severe community acquired pneumonia [as defined by World Health Organization (WHO)] who had not received exclusive breast feeding, had stayed in an overcrowded homes and had an abnormal chest radiograph were more likely to fail to respond with primary antibiotic regimen and require change of antibiotics and prolonged hospital stay. In children with radiographically confirmed pneumonia, lack of breast feeding and low birth weight was associated with need for change in antibiotics.